Navigating the genetic landscape of breast cancer in South Africa amidst a developing healthcare system - Oosthuizen, Jaco; Van der Merwe, Nerina C.; Kotze, Maritha J. (Frontiers in Genetics, 2024)
Breast cancer is a significant global health issue as it represents the leading cause of death in women worldwide. In 2021, the World Health Organization established the Global Breast Cancer Initiative framework with the aim to reduce the breast cancer mortality rate by the year 2040. In countries with developing healthcare systems, such as South Africa, the implementation of first-world technologies has been slow. We provide an overview of the strides taken to improve the cost-effectiveness of genetic service delivery for breast cancer patients in South Africa -from advances in the technology utilized for BRCA founder genotyping to variant screening in moderate-to high-penetrance genes. We furthermore reflect on research undertaken to improve accessibility by means of population-directed point-of-care genetic testing that is ideal for use in a primary healthcare setting. We also report on a pilot study utilizing exome sequencing at the intersection between research and service delivery. Finally, we will discuss and conclude on the controversies, research gaps, and future prospects based on the most recent developments in first-world countries that are implementable in developing countries to improve early detection of breast cancer and overall disease management.